Optimal virtual machine migration - Ng, Li Ting. (2013)
Cloud computing is a large scale distributed computing paradigm in which computing resources are delivered as a service to users over the Internet. It provides an efficient way to dynamically allocate computing resources to meet the demands. Cloud providers offer two different types of payment plans. The payment plans are reservation and on-demand plans. Price of resources in different plan varies. Reservation plan which requires user to reserve in advance offers a lower price as compared to on-demand which ensures availability of resources to the user. An optimal virtual machine placement algorithm is used to minimize the cost spending for each different plan used for hosting virtual machines in a multiple cloud provider environment. It can be applied to cloud computing resource provision to undertake the complexity of optimization problems under uncertainty.